2013
DOI: 10.3384/diss.diva-99958
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of 4D Left Ventricular Blood Flow in Health and Disease

Abstract: The main function of the heart is to pump blood throughout the cardiovascular system by generating pressure differences created through volume changes. Although the main purpose of the heart and vessels is to lead the flowing blood throughout the body, clinical assessments of cardiac function are usually based on morphology, approximating the flow features by viewing the motion of the myocardium and vessels. Measurement of three-directional, three-dimensional and time-resolved velocity (4D Flow) data is feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 90 publications
(88 reference statements)
1
3
0
Order By: Relevance
“…After the initial passive filling has slowed down then diastasis starts and the vortex on the posterior side of the mitral valve completely vanishes while the other on the anterior side continues to grow. The flow rearranges into a single large structure, that is a vortex occupying the whole ventricle and moving from the apex upwards to the aortic channel, in agreement with previous in vivo (Eriksson et al, 2010) and in vitro (Fortini et al, 2013) experiments. Then, another fluid injection is generated by the A-wave, generating a flow dynamics similar to the one produced by the E-wave, but weaker, which further reinforces the large-scale vortex and keeps the recirculation alive during the whole diastole as visible in Fig.…”
Section: Ventricular Hemodynamicssupporting
confidence: 89%
“…After the initial passive filling has slowed down then diastasis starts and the vortex on the posterior side of the mitral valve completely vanishes while the other on the anterior side continues to grow. The flow rearranges into a single large structure, that is a vortex occupying the whole ventricle and moving from the apex upwards to the aortic channel, in agreement with previous in vivo (Eriksson et al, 2010) and in vitro (Fortini et al, 2013) experiments. Then, another fluid injection is generated by the A-wave, generating a flow dynamics similar to the one produced by the E-wave, but weaker, which further reinforces the large-scale vortex and keeps the recirculation alive during the whole diastole as visible in Fig.…”
Section: Ventricular Hemodynamicssupporting
confidence: 89%
“…that the relevant parameter for the MHD effect is the magnitude of the velocity perpendicular to B0. Therefore, the setup was designed to have pulsatile flow with values of the maximum velocity and mean velocity comparable to intracardiac flow velocities in humans . Although such intracardiac blood flow is not everywhere perpendicular to B0 the setup in this work considered the maximum possible MHD effect.…”
Section: Methodsmentioning
confidence: 99%
“…The conservation or loss of kinetic energy during diastole (diastolic KE) is thought to be a more reliable and direct marker of diastolic work than other parameters such as mitral inflow and myocardial velocity (27). Moreover, semi-automatic methods can now obtain KE values with a high degree of reproducibility and accuracy (27)(28)(29), and they have been proven to correlate with mitral inflow and annular velocity (27,30).…”
Section: Left Ventricular Diastolic Kinetic Energymentioning
confidence: 99%
“…In three different studies, Eriksson et al (28,72,74) compared controls to dilated cardiomyopathy patients. They found that in heart failure patients, as the LV dilates, the proportion of non-ejected components increase at the expense of Direct Flow, which is diminished.…”
Section: Flow Component Relative Volumementioning
confidence: 99%